Is there evidence of pessimism in subjective distributions in Singapore? Implications on the equity premium puzzle - Cheong, Allen Yong Fei (2017)
Abel (2002) defines uniform pessimism as the subjective distribution being a leftward shift of the objective distribution. He shows that pessimism in the subjective distribution of growth rate of consumption and output can help resolve the equity premium puzzle. We examine his model and investigate the empirical plausibility of pessimism. We measure the amount of pessimism in the survey data on Singapore’s output and consumption growth. Individual forecasters are in fact proven to be pessimistic.